Genetic and Manual Survey Methods Yield Different and Complementary Views of an Ecosystem - Kelly, Ryan P.; Closek, Collin J.; O'Donnell, James L.; Kralj, James E.; Shelton, Andrew O.; Samhouri, Jameal F. (Frontiers in Marine Science, 2017)
Given the rapid rise of environmental DNA (eDNA) surveys in ecology and environmental science, it is important to be able to compare the results of these surveys to traditional methods of measuring biodiversity. Here we compare samples from a traditional method (a manual tow-net) to companion eDNA samples sequenced at three different genetic loci. We find only partial taxonomic overlap among the resulting datasets, with each reflecting a portion of the larger suite of taxa present in the sampled nearshore marine environment. In the larger context of eDNA sequencing surveys, our results suggest that primer amplification bias drives much of the taxonomic bias in eDNA detection, and that the baseline probability of detecting any given taxon with a broad-spectrum primer set is likely to be low. Whether catching fish with different nets or using different PCR primer sets, multiple data types can provide complementary views of a common ecosystem. However, it remains difficult to cross-validate eDNA sequencing techniques in the field, either for presence/absence or for abundance, particularly for primer sets that target very wide taxonomic ranges. Finally, our results highlight the breadth of diversity in a single habitat, and although eDNA does capture a richer sample of the community than traditional methods of sampling, a large number of eDNA primer sets focusing on different subsets of the biota would be necessary to survey any ecological community in a reasonably comprehensive way.